Excited‐State Intramolecular Proton Transfer: Photoswitching in Salicylidene Methylamine Derivatives. Issue 8 (29th April 2014) - Jankowska, Joanna; Rode, Michał F.; Sadlej, Joanna; Sobolewski, Andrzej L.
Abstract The effect of chemical substitutions on the photophysical properties of the salicylidene methylamine molecule (SMA) (J. Jankowska, M. F. Rode, J. Sadlej, A. L. Sobolewski, ChemPhysChem, 2012, 13, 4287–4294) is studied with the aid of ab initio electronic structure methods. It is shown that combining π‐electron‐donating and π‐electron‐withdrawing substituents results in an electron‐density push‐and‐pull effect on the energetic landscape of the ground and the lowest excited ππ* and nπ* singlet states of the system. The presented search for the most appropriate SMA derivatives with respect to their photoswitching functionality offers an efficient prescreening tool for finding chemical structures before real synthetic realization.